Beyond Depth of Invasion: Adverse Pathologic Tumor Features in Early Oral Tongue Squamous Cell Carcinoma. (14th August 2019) - Larson, Andrew R.; Kemmer, Jacquelyn; Formeister, Eric; El‐Sayed, Ivan; Ha, Patrick; George, Jonathan; Ryan, William; Chan, Emily; Heaton, Chase
Abstract : Objective: In small (≤2 cm) oral tongue squamous cell carcinoma (OTSCC), we sought to clarify the contribution of pathologic features including perineural invasion (PNI), lymphovascular invasion (LVI), and worst pattern of invasion‐5 (WPOI‐5) to clinical outcomes relative to tumor depth of invasion (DOI) of > or ≤ 4 mm. Methods: Cases of ≤2 cm OTSCC treated surgically between 2000 and 2017 at an academic cancer center were reviewed, with retrospective pathologic slide review of DOI, LVI, PNI, and WPOI‐5. Primary outcome measures included occult nodal positivity, 2‐year locoregional recurrence (LRR), disease‐specific survival (DSS), and overall survival (OS). Results: One hundred tumors were included in analyses; 50 had DOI ≤ 4 mm, while 50 had DOI > 4 mm. When DOI was ≤4 mm, the presence of PNI, LVI, or WPOI‐5 was not associated with higher rates of occult cervical metastasis, LRR, or OS. When DOI was >4 mm, there was no difference in rates of occult cervical metastasis or LRR with each feature. On multivariate analysis, only the presence of two or more adverse features was associated with higher LRR (OR 5.7, P = .01) and worse DSS (HR 6.5, P = .02). Conclusion: The rate of occult cervical metastases in small (≤2 cm) OTSCC when DOI is ≤4 mm is very low even when PNI, LVI, or WPOI‐5 is present, and 2‐year LRR is no different. When DOI is >4 mm, the strongest predictor of recurrence and survival on multivariate analysis is the presence of two or more features in the tumor. Level of Evidence: 4 Laryngoscope, 130:1715–1720, 2020